Center-Pivot-Irrigated Sunflowers Cost-Return Budget in Western Kansas - Dumler, Troy J.; Thompson, Curtis R. (My University, 2004)
The cost-return projection estimates the cost of producing center-pivot-irrigated sunflowers in western Kansas.
MF800_2004_10
Keywords: MF800; Economics; Crops; MF